Utilizing steel slag in environmental application – An overview - Lim, Jin Wei; Chew, L. H; Choong, T. S. Y; Tezara, C.; Yazdi, Mohammad H. (IOP Publishing, 2016)
Steel slags are generated as waste material or byproduct every day from steel making industries.The potential environmental issues which are related with the slag dump or reprocessing for metal recovery are generally being focused in the research. However the chemistry and mineralogy of slag depends on metallurgical process which is able to determine whether the steel slag can be the reusable products or not. Nowadays, steel slag are well characterized by using several methods, such as X-ray Diffraction, ICP-OES, leaching test and many more. About the industrial application, it is mainly reused as aggregate for road construction, as armour stones for hydraulic engineering constructions and as fertilizers for agricultural purposes. To ensure the quality of steel slag for the end usage, several test methods are developed for evaluating the technical properties of steel slag, especially volume stability and environmental behaviour. In order to determine its environmental behaviour, leaching tests have been developed. The focus of this paper however is on those applications that directly affect environmental issues including remediation, and mitigation of activities that negatively impact the environment.